Bidirectional associations between circulating vitamin D and cholesterol levels: The Rotterdam Study. Issue 4 (December 2015) - Vitezova, A.; Voortman, T.; Zillikens, M.C.; Jansen, P.W.; Hofman, A; Uitterlinden, A.G.; Franco, O.H.; Kiefte-de Jong, J.C.
Highlights: Total cholesterol levels may be associated with decreased vitamin D levels. The inverse association between HDL cholesterol and vitamin D levels may be bidirectional. The direction of the relation between vitamin D and lipid metabolism may not be that straightforward and may depend on the type of lipids. Abstract: Objectives: Higher levels of vitamin D have been associated with lower rates of cardiovascular disease perhaps through improved lipid profiles. However, results are inconsistent and the direction of the association between vitamin D and lipid levels remains unknown. We examined bidirectional associations between serum 25-hydroxyvitamin D (25(OH)D) and cholesterol concentrations. Study design: We used data from 1165 participants aged 55 to 88 years from the Rotterdam Study, a population-based prospective cohort study. Main outcome measures: Serum concentrations of 25(OH)D, total cholesterol (TC) and HDL cholesterol (HDL-C) were measured at two time points with a median time difference of 6 years. Bidirectional associations between 25(OH)D and each of the blood lipids was examined with path analyses in cross-lagged models. All models were adjusted for baseline age, sex, BMI, smoking status, and diet quality. Results: The best-fit model for 25(OH)D and TC indicated that higher baseline TC concentrations were associated with lower 25(OH)D concentrations (standardized regression coefficient -0.05 (SE 0.02)), but 25(OH)D at baseline did not predict TC. For HDL-C, the best-fit model suggested a bidirectional inverse association between HDL-C and 25(OH)D (standardized regression coefficients of -0.03 (SE 0.02)) for both directions. Conclusions: Our results from path analyses on repeatedly measured 25(OH)D and lipid levels suggest that total cholesterol may be associated with decreased in 25(OH)D concentrations, but not the other way around, whereas the observed inverse association between HDL-C and 25(OH)D may be bidirectional.